Isolated left ventricular non-compaction cardiomyopathy: case report and brief review on diagnostic imaging methods - Borges, José Victor da Nóbrega; Leila, Samira Abdel Correia; Machado, Manuella Guedes da Nóbrega (Brazilian Journal of Case Reports, 2024)
Left ventricular non-compaction cardiomyopathy (LVNC) is a rare congenital heart disease with an estimated incidence of 0.014-0.045% in a general population. It occurs due to a morphogenetic abnormality during embryogenesis that inhibits myocardial compaction and determines prominent trabeculae with deep intertrabecular spaces and thickening of the adjacent myocardium in two distinct layers. Diagnosis is generally established via transthoracic echocardiogram (TTE) with further confirmation with cardiac magnetic resonance (CMR). A 57-year-old male patient previously diagnosed with systemic arterial hypertension and chronic obstructive pulmonary disease reported chest pain and dyspnea upon exertion, headache, and dizziness. During outpatient investigation, the patient was submitted to a stress electrocardiogram that was positive for ischemia and led to a cineangiocoronariography with no signs of coronary artery obstruction. At the echocardiography lab, several trabeculations were detected in the apical region of the left ventricle. A diagnosis of LVNC was established and the results were confirmed via CMR. Management was initiated with the goal of symptom relief. LVNC is a relatively unknown pathology that is frequently underdiagnosed at earlier stages. As presented, we highlight the importance of multimodality imaging, especially TTE and CMR, in the diagnosis of this congenital heart condition.